Diverse Regulation of Temperature Sensation by Trimeric G-Protein Signaling in Caenorhabditis elegans. - Tomoyo Ujisawa; Akane Ohta; Misato Uda-Yagi; Atsushi Kuhara (PLoS ONE, 2016)
Temperature sensation by the nervous system is essential for life and proliferation of animals. The molecular-physiological mechanisms underlying temperature signaling have not been fully elucidated. We show here that diverse regulatory machinery underlies temperature sensation through trimeric G-protein signaling in the nematode Caenorhabditis elegans. Molecular-genetic studies demonstrated that cold tolerance is regulated by additive functions of three Gα proteins in a temperature-sensing neuron, ASJ, which is also known to be a light-sensing neuron. Optical recording of calcium concentration in ASJ upon temperature-changes demonstrated that three Gα proteins act in different aspects of temperature signaling. Calcium concentration changes in ASJ upon temperature change were unexpectedly decreased in a mutant defective in phosphodiesterase, which is well known as a negative regulator of calcium increase. Together, these data demonstrate commonalities and differences in the molecular components concerned with light and temperature signaling in a single sensory neuron.